Estudo sobre a substituição do aço liso pelo bambusa vulgaris, como reforço em vigas de concreto, para o uso em construções rurais - Silva, Osvaldo Ferreira da (2007)
This research verifies the viability technique of the use of the Bambusa vulgaris, vegetal abundant in the state of alagoas, as substitute of the smooth steel, in the reinforcement of the concrete in beams, for use in agricultural constructions. The bamboo comes more than being searched the fifty years, however, exists few studies on this species with this application. The use of materials you renewed and of low consumption of energy it is basic in all the productive areas, mainly of the civil construction, which had the high consumption of energy that this activity requires. This option besides reducing costs, contributes to reduce the effect of the ambient aggression that the production of the steel provokes.The used and widely accepted methodology of the armed concrete is used in this work, with the precautions that if must have with the natural materials, and of heterogeneous mechanical characteristics. With the purpose of if getting a material of better quality, the bamboo was characterized to the traction with knot, using itself 2/3 of the external thickness of colmo.The reinforcement areas are daily pay-definitive, corresponding the percentages of reinforcement of 1%, 2% and 3%, in form of rods, cross-section constant of 0,6 cm x 1,00 cm. It is verified that the sizing of beams of concrete with reinforcement of bamboo, must be made in function of its vertical deformation, in view of its low modulus of elasticity in relation to the steel. To make possible the use of simple and practical form of this material, had been developed tables with sizing of beams, that can be used in some shipment situations, agricultural constructions, or small constructions.